Synchronous lung tumours in a patient with metachronous colorectal carcinoma and a germline MSH2 mutation. Issue 5 (27th April 2009) - Canney, A; Sheahan, K; Keegan, D; Tolan, M; Hyland, J; Green, A
Abstract : Mutations of DNA mismatch repair genes are characterised by microsatellite instability and are implicated in carcinogenesis. This mutation susceptible phenotype has been extensively studied in patients with hereditary non-polyposis colon carcinoma, but little is known of the contribution of such mutations in other tumour types, particularly non-small-cell lung carcinoma. This report describes the occurrence of two synchronous lung tumours, one mimicking a metastatic colon carcinoma, in a male patient with a history of metachronous colonic carcinoma. Immunohistochemistry supported a pulmonary origin for both lesions. Mismatch repair protein immunohistochemistry showed loss of MSH2 and MSH6 expression in both colonic tumours and in one lung tumour showing enteric differentiation. Subsequent mutational analysis demonstrated a deleterious germline mutation of the MSH2 mismatch repair gene. The significance of these findings and the practical diagnostic difficulties encountered in this case are discussed.